APPLICATION OF MAGIC BALL-BASED GROUP INVESTIGATION MODELS TO IMPROVE COLLABORATIVE SKILLS AND STUDENT LEARNING MATHEMATICS RESULTS - Rusmidah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by teacher-centered learning, which caused the lack of student activity in solving problems and finding answers together. This research aims to improve mathematical collaborative skills and student learning outcomes through the application of a magic ball-assisted group investigation learning model. The subject of the research was a classroom action research study on third-grade students at SDN 008 Talang Perigi. The instruments used were observation sheets and learning outcomes tests. The results showed that in the first cycle, students’ collaborative mathematical skills obtained an average of 55.77% in the high category, and in the second cycle increased to 73.44% in the very high category. Student learning outcomes in the first cycle had an average of 67.83 with a classical completeness of 53%, increasing in the second cycle to 75.67 with a classical completeness of 83%. Based on the findings, it can be concluded that the application of the group investigation learning model assisted by a magic ball can improve the collaborative mathematical skills and learning outcomes of third-grade students at SDN 008 Talang Perigi.